The complete poems and translations - Marlowe, Christopher, 1564-1593.; Orgel, Stephen (New York : Penguin Books, 2007)
This anthology offers a comprehensive look at the poems of Christopher Marlowe, one of England's great poets and playwrights.
Introduction / by Stephen Orgel -- Table of dates -- Hero and Leander -- George Chapman continuation of Hero and Leander -- Henry Petowe: The Second Part of Hero and Leander, Containing Their Further Fortunes -- All Ovid's Elegies -- Lucan's First Book -- From The Passionate Pilgrim -- The Passionate Shepherd to His Love -- Sir Walter Ralegh (attrib.): The Nymph's Reply -- Anonymous: Another of the Same Nature, Made Since -- John Donne: The Bait -- J. Paulin: Love's Contentment -- On the Death of Sir Roger Manwood -- Notes -- Dictionary of classical names.
Keywords: Poetry; Marlowe, Christopher; Lyrik; 2; Poetry